2015 IEEE International Conference on Self-Adaptive and Self-Organizing Systems Workshops 2015
DOI: 10.1109/sasow.2015.14
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Resilience Properties of Different Topologies of Collective Adaptive Systems

Abstract: Abstract-Modern software systems are often compositions of entities that increasingly use self-adaptive capabilities to improve their behavior to achieve systemic quality goals. Selfadaptive managers for each component system attempt to provide locally optimal results, but if they cooperated and potentially coordinated their efforts it might be possible to obtain more globally optimal results. The emergent properties that result from such composition and cooperation of self-adaptive systems are not well unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…PRISM-games (2) enables the modelling and analysis of TSGs against the extended PRISM logic (see Definition 11) and multi-objective specifications. Applications using TSGs and PRISM-games to model autonomous systems include autonomous urban driving (72), smart grids (65), human-in-the-loop planning (75,76), managing collections of autonomic systems (77,78) and self-adaption (79). In addition, GIST (80) allows the analysis of ω-regular properties of TSGs and GAVS+ ( 81) is a generalpurpose tool for algorithmic game solving including TSGs.…”
Section: Extensionsmentioning
confidence: 99%
“…PRISM-games (2) enables the modelling and analysis of TSGs against the extended PRISM logic (see Definition 11) and multi-objective specifications. Applications using TSGs and PRISM-games to model autonomous systems include autonomous urban driving (72), smart grids (65), human-in-the-loop planning (75,76), managing collections of autonomic systems (77,78) and self-adaption (79). In addition, GIST (80) allows the analysis of ω-regular properties of TSGs and GAVS+ ( 81) is a generalpurpose tool for algorithmic game solving including TSGs.…”
Section: Extensionsmentioning
confidence: 99%
“…They found that there is an optimum number of (Sharman and Yassine, 2004) Simple bus, multiple bus, auxiliary or weak or subsidiary buses, planar triangular clusters, tetrahedron of clusters, three-level design hierarchy. (Yassine and Naoum-Sawaya, 2016) Random, diagonal, block diagonal, local, hierarchical, dependent, small world, scale-free (Hölttä-Otto et al, 2012) Integral, bus-like, modular (Min et al, 2016) Integral, linear-modular, bus-modular (Rivkin and Siggelkow, 2007) Random, local, small-world, block-diagonal, preferential attachment, scale-free, centralised, hierarchical, diagonal, dependent (Glazier et al, 2015) Ring, mesh, star, fully connected, line, tree bus (Selva et al, 2016) Combining, assigning, partitioning, down-selecting, connecting (bus and star, ring, mesh tree), permuting (Baldwin et al, 2014) Core periphery, multi-core, hierarchical hubs that will give a positive influence on quality, highlighting the importance of the management of hubs during the early design stages. Network science studies of hubs in engineering systems include Braha & Bar-Yam (2004a, Mehrpouyan et al (2014), Braha (2016) and Piccolo et al (2018).…”
Section: Hubsmentioning
confidence: 99%
“…In the scenario [28], an external attacker uses a dened amount of available resources to attempt to breach members of the CAS (e.g., by placing a high number of requests). Each CAS member has the ability to detect the attack, defend itself against it by employing a xed set of defense resources, and has the ability to notify other members of the CAS of the attack.…”
Section: Case Studiesmentioning
confidence: 99%
“…This contrasts with ad-hoc solutions that demand developing specic infrastructure and are error-prone. The analysis of a CAS scenario similar to the one in Section 6.1.3 [28] required combining the PRISM preprocessor [48] with scripts that demanded topologies to be encoded as matrixes in separate text les, leading to multiple trial and error rounds (due to errors in matrix encodings, script tuning). For TAS, the problem has also been solved employing a custom template engine and a python script that generates probabilistic models based on analysis of Alloy specications [15].…”
Section: (Rq3)mentioning
confidence: 99%